Implementation of Principal Management Strategies in Improving Teacher Performance at SD Negeri Titih Lor 03 - Wulandari, Wiwit Viana; Aryani, Ine Kusuma (Proceedings Series on Social Sciences & Humanities, 2025)
This study aims to describe the principal's leadership management practices in improving teacher performance at SD Negeri Tiritih Lor 03. The principal's managerial skills will determine teacher performance. Using a qualitative approach, this research focuses on an in-depth understanding of the management strategies implemented by the principal and their impact on teacher performance. We collected data through observation, interviews with the principal and teachers, and documents related to the school program. The data were analyzed using a qualitative descriptive approach to see the tendency of the principal's leadership management strategies and their application in improving teacher performance. The results of this study show that principals conduct several policy strategies through planning, organizing, mobilizing, and supervising to improve teacher performance.